Perlindungan Hak Konstitusional Pekerja dalam Putusan Mahkamah Konstitusi tentang Outsourcing dan Omnibus Law - Salsabila Hadi Aulia; Dedi Mulyadi; Camiliya Fakhriyah Garnita; Fina Asriani; Muhamad Fahri Mawardi; Muhammad Abhiansyah Damar Nagara (Journal of Contemporary Law Studies, 2026)
This study aims to analyze the protection of workers’ constitutional rights in the Constitutional Court decisions regarding outsourcing and the Omnibus Law in Indonesia. The research focuses on outsourcing regulations, the legal considerations of the Constitutional Court, and the implications of its decisions for workers’ rights protection. This study employs normative legal research using statutory and case approaches through the analysis of legislation, constitutional provisions, and Constitutional Court decisions, particularly Decision Number 27/PUU-IX/2011 and Decision Number 168/PUU-XXI/2023. The findings show that the Constitutional Court recognizes outsourcing as constitutionally valid as long as it does not violate workers’ constitutional rights, including fair treatment, job security, and decent working conditions as guaranteed by the 1945 Constitution of the Republic of Indonesia. The Court also emphasizes the application of the Transfer of Undertaking Protection of Employment (TUPE) principle to ensure the continuity of workers’ rights in outsourcing practices. Furthermore, the Omnibus Law increases labor flexibility, which potentially weakens workers’ protection and creates legal uncertainty. In conclusion, the Constitutional Court plays an important role in balancing economic interests with the protection of workers’ constitutional rights in Indonesia’s labor system.